Development and evaluation of a sepsis simulation with undergraduate nursing students - Martinez, Kelly; Aronson, Barbara (Nurse Education Today, 2024)
Background In 2016, the Centers for Disease Control found that more than 1.5 million people develop sepsis each year and about 250,000 Americans die from it. Early identification and treatment of sepsis can decrease mortality and morbidity, yet studies have shown student nurses are not prepared to rescue deteriorating patients. Method The purpose of this pilot study was to create and test a response to rescue simulation for use with undergraduate nursing students. The simulation depicted a patient deteriorating from sepsis. The Martinez Sepsis Competency Evaluation Tool (MSCET) developed to rate student behaviors during the simulation. Promoting Excellence and Reflective Learning in Simulation (PEARLS) debriefing model was used post simulation. Results The overall content validity of the MSCET was 0.88. Each item that scored a I-CVI of 0.78 or less were revised. The total percentage of behaviors met was 68 %. The inter-rater reliability of the MSCET conciseness was 0.47 (X = 67.508, df = 48, p ≤ .05). Conclusion The results indicate the simulation based experience was effective in preparing students to care for patients with early signs of sepsis. Students were complimentary about the experience, and preliminary data on the MSCET psychometrics were positive. Limitations of the study and recommendations for further revision of the simulation were made.
Keywords: Debriefing; Deterioration; Instrument development; Observers; Patient deterioration; Recognizing; Responding; Sepsis; Simulation; Undergraduate nursing students; Video-recorded; dept.nur; peer-reviewed

Humanizing substance abuse: a theory-based educational intervention for undergraduate nursing students - Roncallo, Hannah R.; Aronson, Barbara (Journal of Addictions Nursing, 2023)
Background Healthcare providers, as well as healthcare students, have been found to harbor negative attitudes toward individuals with substance abuse disorders, impacting the care they give and subsequently creating poor patient outcomes. Purpose This study seeks to determine the effectiveness of an educational intervention, grounded in theory, toward changing nursing student attitudes regarding patients with a substance abuse disorder. Methods Nursing students participated in a teaching intervention, developed using the experiential learning theory, that utilizes modalities for each kind of learner aimed at reducing bias toward this population. The Medical Condition Regard Scale was used pre/post intervention to determine regard toward patients with the diagnosis of substance abuse. Results Student nurses maintained the least favorable attitudes toward individuals who abuse substances in comparison with patients with the diagnoses of pneumonia or gastroesophageal reflux disease; there were significant differences in attitudes toward patients who abused substances before and after participation in the educational intervention, with postparticipation attitudes being significantly more positive than attitudes before participation. Students found the educational intervention and debriefing highly satisfactory. Implications This educational intervention can provide a cost-effective, easy-to-replicate, time-efficient learning activity that could be added to undergraduate nursing curriculum.
Keywords: dept.nur; peer-reviewed

The Effects of a Deliberate Practice Debriefing During a Response to Rescue Patient Simulation With Undergraduate Nursing Students - Aronson, Barbara; Bell, Arleigh; Andrighetti, Tia; Meyer, Mary; Shepherd, Karen; Bambini, Deborah (Nursing Education Perspectives, 2021)
The purpose of this multisite, randomized, pretest/posttest quasi-experimental study was to compare student nurse competency, learning retention, and perceived student support after exposure to a deliberate practice debriefing versus standardized debriefing. Fifty undergraduate students participated in the complex response to rescue simulation. The intervention group had significantly higher total mean and three subscale scores on the competency tool than the comparison group, although differences in learning retention and student support were not significant. This study provides preliminary support for the effectiveness of deliberate practice debriefing to enhance students’ mastery of skills and behaviors in complex simulations.
Keywords: Baccalaureate; Clinical Competence; Education; Humans; Nurses; Nursing; Patient Simulation; Simulation Training; Students; clinical competence; dept.nur; human; nurse; nursing education; nursing student; patient simulation; peer-reviewed; simulation training